PELATIHAN TATA RIAS DAN BUSANA PERTUNJUKAN PADA GURU SEKOLAH DASAR KECAMATAN GAYAMSARI SEMARANG - R. Soeyono; Riris Setyo Sundari; Ervina Eka Subekti; Ryky Mandar Sary; Mei Fita Asri Untari (Universitas PGRI Semarang, 2011)
Abstract Being able to organize the fashion including makeup of the elementary students in their show is the aim of this community service. In exploring the students?óÔé¼Ôäó talent, the school needs to have a show for them like dancing show. This program was held at elementary schools in Gayamsari Semarang. Team of community service found that there are still less skill in arranging the fashion and makeup for their own students before they perform on the stage. Team taught that the elementary teachers need to equip this skill in order to prepare and help them in dressing fashion and makeup of the show. In this program also train them how to choose a wardrobe/ proper fashion, how to dress the performer, and how to mix and match the fashion and its makeup, etc. The training was held in February 19th 2011 and it was attended by 25 participants. Each participant looks very enthusiastic and wondering to get every session of trainings. ?é?á Key Word: fashion and makeup, dancing show, performance